2017
DOI: 10.1111/jcpp.12713
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Childhood maltreatment, latent vulnerability and the shift to preventative psychiatry – the contribution of functional brain imaging

Abstract: Background: Childhood maltreatment is a potent predictor of poor mental health across the life span. We argue that there is a need to improve the understanding of the mechanisms that confer psychiatric vulnerability following maltreatment, if we are to progress from simply treating those with a manifest disorder, to developing effective preventative approaches that can help offset the likelihood that such disorders will emerge in the first place. Methods: We review extant functional neuroimaging studies of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
245
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(297 citation statements)
references
References 151 publications
(214 reference statements)
15
245
0
17
Order By: Relevance
“…Initial cognitive impairment had largely resolved by young adulthood (Sonuga-Barke et al, 2017). Interestingly, problems of anxiety and mood, most commonly associated with HPA axis dysregulation were absent in this group during childhood and early adolescence, but emerged very strongly in adulthood in a way that was consistent with a model of latent vulnerability (McCrory et al, 2017;SonugaBarke et al, 2017).…”
Section: Introductionsupporting
confidence: 74%
“…Initial cognitive impairment had largely resolved by young adulthood (Sonuga-Barke et al, 2017). Interestingly, problems of anxiety and mood, most commonly associated with HPA axis dysregulation were absent in this group during childhood and early adolescence, but emerged very strongly in adulthood in a way that was consistent with a model of latent vulnerability (McCrory et al, 2017;SonugaBarke et al, 2017).…”
Section: Introductionsupporting
confidence: 74%
“…Those thought to have callous and unemotional traits are subject to specific study (Viding & McCrory, ). Identifying factors associated with offending behaviour should inform developing early intervention for those at risk by managing the risk factors (Lahey, Rathouz, Applegate, Tackett, & Waldman, ; Rhee et al, ) or pathways of pathogenesis (McCrory, Gerin, & Viding, ). We suggest an additional need to identify protective/resilience factors in those with identified risk factors who avoid offending behaviour; knowing what has protected some can inform early intervention and support for others.…”
Section: Service and Research Contextmentioning
confidence: 99%
“…Although not routinely used in psychology or psychiatry research, this recommendation to use machine learning techniques may be particularly worthwhile for the field of child maltreatment, where there is little psychometric research on measures. In a paper for the Journal of Child Psychology and Psychiatry , McCrory, Gerin, and Viding () called attention to the measurement of emotional abuse using self‐report instruments. Using the Childhood Trauma Questionnaire (CTQ) to illustrate their points, they noted that more than half of over 2000 male adolescents met the threshold for ‘severe’ or ‘extreme’ emotional abuse (Mikaeili, Barahmand, & Abdi, ) and suggested that the CTQ was not able to differentiate between common experiences for many children that may be unkind or other experiences that may reflect a denigrating or humiliating pattern of treatment.…”
mentioning
confidence: 99%
“…McCrory et al (2017) expressed another concern that the emotional abuse items 'potentially conflate depressive schemas capturing the expectation (rather than the reality) that others will hurt, abuse, humiliate, cheat, lie, manipulate or take advantage (van Vlierberghe, Braet, Bosmans, Rosseel, & Bogels, 2010) with actual experiences of emotional abuse' (page 351). McCrory et al (2017) argued that measurement of emotional abuse in particular warrants appropriate use of stringent thresholds, structured interviews and/or independent verification, and new research focusing on the psychometric properties of the emotional abuse.…”
mentioning
confidence: 99%